2021
DOI: 10.6018/analesff.483991
|View full text |Cite
|
Sign up to set email alerts
|

Apprentissage immersif du FLE: potentiels des applications et scénario ludo-éducatif.

Abstract: Nuestro grupo de investigación, LCF, está interesado en abordar la temática de la realidad virtual bajos sus diferentes formas, como los videojuegos, la realidad aumentada, en la enseñanza de una lengua extranjera, pensando que podría ser la solución para nuestros estudiantes. En efecto, pueden abordar, en nuestro caso, el francés, desde la gamificación y, por tanto, desde la motivación. Además, tiene la ventaja de poder llevar el aprendizaje al terreno de la autonomía y, sobre todo, de la inmersión, concepto … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 2 publications
1
0
0
Order By: Relevance
“…Similarly, 5 articles were found for the factors: scanning of QR codes that allow a better grasp of the topics, optimal model, iterative, attractive, and motivating, respectively. RQ2, allowed for the identification of the various factors that improve the learning of the Quechua language, as shown in Figure 11 It was found that the application of AR for learning allows combining the real and virtual world allowing to attract the student's interest [65] in this sense [22][45] mentioned the ease of scanning 3D animations which is attractive and motivating for the students, likewise in [53][54] it was found that these animations allow enjoying the acquired knowledge and even in the visualizations they generate that the student wants to investigate more about the subject, This agrees with [61] who found that the use of 3D animations, texts, video, and audio generate critical reasoning, in [75] they allowed a better conceptualization of terms and in [73] it generated feedback and a motivating study habit, all of which resulted in an interesting, easy to use and attractive tool. Figure 10 shows the number of articles for each factor to enhance learning with AR.…”
Section: Manuscript Analysissupporting
confidence: 53%
“…Similarly, 5 articles were found for the factors: scanning of QR codes that allow a better grasp of the topics, optimal model, iterative, attractive, and motivating, respectively. RQ2, allowed for the identification of the various factors that improve the learning of the Quechua language, as shown in Figure 11 It was found that the application of AR for learning allows combining the real and virtual world allowing to attract the student's interest [65] in this sense [22][45] mentioned the ease of scanning 3D animations which is attractive and motivating for the students, likewise in [53][54] it was found that these animations allow enjoying the acquired knowledge and even in the visualizations they generate that the student wants to investigate more about the subject, This agrees with [61] who found that the use of 3D animations, texts, video, and audio generate critical reasoning, in [75] they allowed a better conceptualization of terms and in [73] it generated feedback and a motivating study habit, all of which resulted in an interesting, easy to use and attractive tool. Figure 10 shows the number of articles for each factor to enhance learning with AR.…”
Section: Manuscript Analysissupporting
confidence: 53%